2000
DOI: 10.1093/brain/123.9.1903
|View full text |Cite
|
Sign up to set email alerts
|

Functional delineation of the human occipito-temporal areas related to face and scene processing: A PET study

Abstract: By measuring regional cerebral blood flow using PET, we delineated the roles of the occipito-temporal regions activated by faces and scenes. We asked right-handed normal subjects to perform three tasks using facial images as visual stimuli: in the face familiar/unfamiliar discrimination (FF) task, they discriminated the faces of their friends and associates from unfamiliar ones; in the face direction discrimination (FD) task, they discriminated the direction of each unfamiliar face; in the dot location discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
161
1
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(179 citation statements)
references
References 55 publications
12
161
1
4
Order By: Relevance
“…Again, the research to date is not conclusive, but neural and perceptual systems that accommodate these and other forms of variability (e.g., dialect differences) within broader constraints are evident for speech (Doupe & Kuhl, 1999), face recognition (Nakamura et al, 2000), and gesture (McNeill, 2000). Social and cognitive research suggests plasticity in the ability to form categories related to tool use (Bloom, 1996) and social competition (Stephan, 1985), among other things.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the research to date is not conclusive, but neural and perceptual systems that accommodate these and other forms of variability (e.g., dialect differences) within broader constraints are evident for speech (Doupe & Kuhl, 1999), face recognition (Nakamura et al, 2000), and gesture (McNeill, 2000). Social and cognitive research suggests plasticity in the ability to form categories related to tool use (Bloom, 1996) and social competition (Stephan, 1985), among other things.…”
Section: Discussionmentioning
confidence: 99%
“…Maguire et al (1998) also provided evidence for distinct brain systems involved in representing physical space (especially the right hippocampus and right inferior parietal cortex) and for speed of movement in this space (especially the right caudate nucleus). Nakamura et al (2000) found that regions of the left and right parietal-occipital junctions and portions of the left and right hippocampi were engaged during the processing of scenes and that these regions differed from those engaged during the processing of faces or objects. Recent demonstrations of injury-related functional dissociations between knowledge about tools (e.g., name, description of their use) and the actual use of tools suggests that distinct systems of brain regions support these distinct competencies (Hodges, Spatt, & Patterson, 1999; see also Lockman, 2000).…”
Section: Physical Systemsmentioning
confidence: 97%
“…Separation of the correlates of recognition and naming in functional imaging studies will call for designs that overcome such "automatic" processing. A possible exception in this regard is the PET study of Nakamura et al [2000]. Normal subjects performed three discrimination tasks: deciding whether a presented face is that of a personally familiar person or an unfamiliar person, deciding whether an unfamiliar face faces left or right, and deciding whether a dot superimposed on a scrambled face is on the right or left of the screen.…”
Section: Discussionmentioning
confidence: 99%
“…However, while these studies demonstrated relevant time epochs, the localization of these processes needs to be done using complementary techniques. Thus, over the last 10 to 20 years, positron emission tomography (PET) and functional MRI studies looked further into the anatomical correlates in vivo (12)(13)(14). While the underlying brain structures can now be precisely localized to within a precision of a few millimeters, no information about the temporal aspects of face processing was obtained using these techniques.…”
mentioning
confidence: 99%